Validation and clinical application of a molecular method for the identification of Cryptococcus neoformans/Cryptococcus gattii complex DNA in human clinical specimens (2015)
ABSTRACT: The diagnosis of cryptococcosis is usually performed based on cultures of tissue or body flu-ids and isolation of the fungus, but this method may require several days. Direct microscopicexamination, although rapid, is relatively insensitive. Biochemical and immunodiagnosticrapid tests are also used. However, all of these methods have limitations that may hinderfinal diagnosis. The increasing incidence of fungal infections has focused attention on toolsfor rapid and accurate diagnosis using molecular biological techniques. Currently, PCR-basedmethods, particularly nested, multiplex and real-time PCR, provide both high sensitivity andspecificity.In the present study, we evaluated a nested PCR targeting the gene encoding the ITS-1and ITS-2 regions of rDNA in samples from a cohort of patients diagnosed with cryptococ-cosis. The results showed that in our hands, this Cryptococcus nested PCR assay has 100%specificity and 100% sensitivity and was able to detect until 2 femtograms of CryptococcusDNA.© 2015 Elsevier Editora Ltda. All rights reserved.IntroductionCryptococcosis is a fungal infection caused by encapsu-lated yeasts of the phylum Basidiomycota, genus Cryptococcus.∗Corresponding author at: Grupo de Micología Médica y Experimental, Corporación para Investigaciones Biológicas, Carrera 72aNo.78b-141, Medellín, Colombia.E-mail address: tnaranjo@cib.org.co (T. Naranjo).Although over 30 different species of Cryptococcus have beenidentified to date, just two closely related species – Cryptococ-cus neoformans and Cryptococcus gattii – cause the majority ofhuman fungal infections.1–3Based on specific polysaccharidecapsule antigen analysis, subtyping data, and comparisonshttp://dx.doi.org/10.1016/j.bjid.2015.07.0061413-8670/© 2015 Elsevier Editora Ltda. All rights reserved.